Use of Cytokine Mix-, Imiquimod-, and Serum-Induced Monoculture and Lipopolysaccharide- and Interferon Gamma-Treated Co-Culture to Establish In Vitro Psoriasis-like Inflammation Models - Katarzyna Bocheńska (MDPI AG, 2021)
Psoriasis (Ps), commonly perceived as a skin and joint disorder, has a complex basis and results from disturbances in the sophisticated network between skin and the immune system. This makes it difficult to properly depict the complete pathomechanism on an in vitro scale. Deciphering the complicated or even subtle modulation of intra- and intercellular factors, assisted by the implementation of in vitro human skin models, may provide the opportunity to dissect the disease background step by step. In addition to reconstructed artificial skin substitutes, which mimic the native physiological context, in vitro models are conducive to the broad “3 Rs” philosophy (reduce, refine, and replace) and represent important tools for basic and applied skin research. To meet the need for a more comprehensive in vitro Ps model, a set of various experimental conditions was applied in this study. The selection of in vitro treatment that mimicked the Ps phenotype was illustrated by analyses of discriminating biomarker genes involved in the pathogenesis of the disease, i.e., keratinocyte differentiation markers, antimicrobial peptides, chemokines, and proliferation markers. This resulted in a reproducible protocol for the use of the primary skin keratinocyte (pKC) monoculture treated with a cytokine cocktail (5MIX, i.e., interleukin (IL) 1 alpha (IL-1α), IL-17A, IL-22, oncostatin M (OSM), and tumour necrosis factor alpha (TNF-α)) at a calcium (Ca2+) concentration (i.e., 2 mM) in an applied medium, which best mirrored the in vitro Ps-like inflammatory model. In addition, based on waste skin material, the method has the potential for extensive experimentation, both in detailed molecular studies and preclinical tests.